Analysis of Factors Related to Stunting Incidence in Toddlers Aged 24-59 Month - Tri Suci; Ermi Girsang; Ali Napiah Nasution; Irza Haicha Pratama (Proceeding of the International Conference on Health Sciences and Nursing, 2025)
Stunting is a critical global health issue, especially in developing countries, affecting the growth and development of children under five. This study aims to analyze the factors related to the incidence of stunting in toddlers aged 24-59 months. This quantitative research employs a cross-sectional design, involving 200 toddlers selected randomly from several integrated health posts (Posyandu). Data were collected through questionnaires and direct measurements, then analyzed using multiple logistic regression. The results showed that family nutritional awareness behavior, maternal nutritional knowledge, and clean and healthy living behavior (CHLB) significantly affect the incidence of stunting. Maternal nutritional knowledge was identified as the most dominant factor. These findings emphasize the importance of comprehensive interventions involving family education, nutritional support, and CHLB promotion to reduce stunting prevalence. Further research and implementation of targeted interventions are needed to address and mitigate stunting effectively.